2020
DOI: 10.1111/apt.15925
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: limited benefits from early colonoscopy in acute lower gastrointestinal bleeding

Abstract: Background:The optimal timing of colonoscopy in acute lower gastrointestinal bleeding (LGIB) remains controversial.Aim: To characterise the utility of early colonoscopy (within 24 hours) in managing acute LGIB. Methods:A systematic literature search to October 2019 identified fully published articles and abstracts of randomised controlled trials (RCTs) and observational studies with control groups assessing early colonoscopy in acute LGIB. The primary outcome was rebleeding. Secondary outcomes included mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 48 publications
3
29
0
Order By: Relevance
“…However, a statistical analysis was not performed to specifically evaluate this result. Another recent meta-analysis studied impact of timing on LOS for RCTs and observational studies separately: no difference in LOS was found for RCTs only, but when only observational studies were analyzed, LOS was statistically reduced [34]. In our study, we found that EC was associated with a substantially decreased hospital LOS (by 1.6 days) in comparison to late colonoscopy, consistent with several other studies [15,[20][21][22][23].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, a statistical analysis was not performed to specifically evaluate this result. Another recent meta-analysis studied impact of timing on LOS for RCTs and observational studies separately: no difference in LOS was found for RCTs only, but when only observational studies were analyzed, LOS was statistically reduced [34]. In our study, we found that EC was associated with a substantially decreased hospital LOS (by 1.6 days) in comparison to late colonoscopy, consistent with several other studies [15,[20][21][22][23].…”
Section: Discussionsupporting
confidence: 89%
“…The possibility that earlier endoscopic intervention can lead to rapid identification and control of culprit lesion bleeding and consequently could lead to reduced mortality in patients with LGIB makes timing of colonoscopy a critical point and area of interest in management of LGIB. Four RCTs 10 11 13 14 , six observational studies 15 20 21 25 26 27 and seven meta-analyses 28 29 30 31 32 33 34 have been performed to evaluate this issue. One RCT showed that urgent colonoscopy led to identification of a definitive source of bleeding more frequently, but it did not lead to lower mortality 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available evidence comparing early vs. elective colonoscopy in the management of patients with acute LGIB consists of seven systematic reviews with meta-analyses [55][56][57][58][59][60][61], four RCTs [51,[62][63][64], and 16 observational studies [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] (Table 7 s). Patients with "minor" LGIB managed as outpatients and patients with an UGIB source were excluded from the RCTs [51,[62][63][64] and most of the observational studies [66,67,69,[71][72][73][74][75][76][77][78].…”
Section: What Is the Appropriate Timing For Colonoscopy In Patients With Acute Lower Gastrointestinal Bleeding?mentioning
confidence: 99%
“…Recent meta-analyses report that early colonoscopy within 24 hours does not improve clinical outcomes 1 2 . Holzwanger et al suggest a conservative approach for SARS-CoV-2-positive patients with acute LGIB 3 , but no advice is provided on management and outcomes of patients who remain hemodynamically unstable after adequate resuscitation.…”
mentioning
confidence: 99%